Characterizing the Optimal Diversity Training Programs for Physicians: A Survey sponsored by Pacific Spine and Pain Society - Gendreau JL; Bauman MMJ; Brown NJ; Alfonzo Horowitz M; Chakravarti S; Mehkri Y; Grovey B; Lee E; Lee G; Cornidez E; Bhandal HS; Pope JE (Journal of Pain Research)
Julian L Gendreau,1 Megan MJ Bauman,2 Nolan J Brown,3 Melanie Alfonzo Horowitz,4 Sachiv Chakravarti,5 Yusuf Mehkri,6 Brittany Grovey,7 Eric Lee,8 Gemayel Lee,7 Eric Cornidez,9 Harjot S Bhandal,10 Jason E Pope10 1Whiting School of Engineering, Johns Hopkins, Baltimore, MD, USA; 2School of Medicine, Mayo Clinic, Phoenix, AZ, USA; 3Department of Neurological Surgery, University of California, Irvine, CA, USA; 4Department of Neurological Surgery, Johns Hopkins, Baltimore, MD, USA; 5Johns Hopkins University, Baltimore, MD, USA; 6University of Florida School of Medicine, Gainesville, FL, USA; 7Relive You Center for Advanced Pain Management, San Diego, CA, USA; 8Miliani Pain Center, Miliani, HI, USA; 9Pain Institute of Southern Arizona, Tucson, AZ, USA; 10Evolve Restorative Center, Santa Rosa, CA, USACorrespondence: Jason E Pope, Evolve Restorative Center, Santa Rosa, CA, USA, Tel +1 615-521-0777, Email popeje@me.comIntroduction: Recently, increasing research has shown inferior outcomes in patients with respect to specific social determinants of health. Therefore, optimizing diversity training given to pain management providers is imperative for physicians to provide culturally competent healthcare and to improve patient outcomes. In this paper, we attempt to describe trends in the Pacific Spine and Pain Society (PSPS) membership to help discover optimal diversity education paradigms for pain management providers by performing a survey on behalf PSPS.Methods: A survey was disseminated to all members of the PSPS at the 2022 annual meeting. Opinions were solicited with respect to respondents’ demographics, diversity training type, diversity training timing, and how this correlates with a respondent’s self-reported confidence in navigating diversity issues in the workplace. Cronbach’s alpha test was used to rate internal consistency while logistic regression models were used for statistical analysis.Results: Cronbach’s alpha produced a rating of 0.91. A total of 164 individuals responded to the survey, with 115 (70%) being male and 98 (60%) did not consider themselves to be under-represented in medicine. Survey respondents who obtained diversity training post-fellowship (p = 0.004) and with interactive training type (p = 0.010) self-reported to be more confident in handling matters of diversity in the workplace. Respondents who were underrepresented (p = 0.018), females (p = 0.033), practice in the west coast (p = 0.036), academic practice (p=0.031), and non-rural areas (p = 0.033) were also found to be more confident in handling matters of diversity.Conclusion: Practitioners who received diversity training post-fellowship and with interactive and role model formats felt most confident to handle matters of diversity. Underrepresented groups, females, individuals from non-rural practices and individuals from academic practices appear to feel more confident in handling these issues.Keywords: bias, competency, cultural training, diversity, education, medicine, survey, workforce